دراسة شعاعية عن التشريح القنوي وعدد الجذور وتصنيفها في الضواحك الأولى العلوية في عينة من المجتمع السوري باستخدام التصوير الشعاعي المخروطي المحوسب CBCT (مجلة جامعة حماة, 2024)
Due to the fact that the morphology of the roots is very variable and complex, many descriptive laboratory studies have been conducted in order to better understand the internal anatomy of the root, the purpose of this study was to evaluate the number of roots and canal configuration of maxillary first premolar and their symmetry in the male and female sexes among Syrian population. The study sample consisted of 563 CBCT images (370 images for females – 193 images for males). The images were reviewed by two endodontists. Details of gender, root number and canal configuration in each root according to Vertucci classification were recorded by studying the image according to all levels (Axial Coronal_Sagittal_Oplique_3D). Statistical analysis was performed with SPSS, then the chi-square test was used. The largest proportion of the shape of the upper first premolars within the studied sample was the shape of the two separate roots (males by 72.7% and females by 72.1% and in the whole sample by 72.2%). While the single root form was less widespread (in males 23.4%, in females 19.5% and in the whole sample 20.7%). Then it is followed by the least widespread ratio of the shape of the three roots shape (in males 3.9%, females 8.4% and in the entire sample 7.1%). The most common form in both sexes was the two separate roots with one canal in each of (Type IV), followed by a single root with two (Type II) channels, followed by three roots with three canals of Type (I) in each of.
Keywords: three-dimensional images (CBCT), maxillary first premolars, Vertucci classification.